DAMPAK KEBERADAAN INFRASTRUKTUR TERHADAP PENINGKATAN PRODUKSI DAN LUAS LAHAN SAWIT - Andi Irawan (Jurnal Agrisep)
The purpose of this research was analyzing the impact of the existence of infrastructures such as construction, electrical, highway (state, province and regency city road ), Transport and Telecommunication sectors on the production and areal expansion of oil palm plantations in both South Sumatera and Bengkulu.